Protocol for a systematic review of evaluation research for adults who have participated in the 'SMART recovery' mutual support programme. Issue 5 (23rd May 2016) - Beck, Alison K; Baker, Amanda; Kelly, Peter J; Deane, Frank P; Shakeshaft, Anthony; Hunt, David; Forbes, Erin; Kelly, John F
Abstract : Introduction: Self-Management and Recovery Training (SMART Recovery) offers an alternative to predominant 12-step approaches to mutual aid (eg, alcoholics anonymous). Although the principles (eg, self-efficacy) and therapeutic approaches (eg, motivational interviewing and cognitive behavioural therapy) of SMART Recovery are evidence based, further clarity regarding the direct evidence of its effectiveness as a mutual aid package is needed. Relative to methodologically rigorous reviews supporting the efficacy of 12-step approaches, to date, reviews of SMART Recovery have been descriptive. We aim to address this gap by providing a comprehensive overview of the evidence for SMART Recovery in adults with problematic alcohol, substance and/or behavioural addiction, including a commentary on outcomes assessed, potential mediators, feasibility (including economic outcomes) and a critical evaluation of the methods used. Methods and analysis: Methods are informed by the Cochrane Guidelines for Systematic Reviews and the Preferred Reporting Items for Systematic Reviews and Meta-Analysis statement. 6 electronic peer-reviewed and 4 grey literature databases have been identified. Preliminary searches have been conducted for SMART Recovery literature (liberal inclusion criteria, not restricted to randomised controlled trials (RCTs), qualitative-only designs excluded). Eligible 'evaluation' articles will be assessed against standardised criteria and checked by an independent assessor. The searches will be re-run just before final analyses and further studies retrieved for inclusion. A narrative synthesis of the findings will be reported, structured around intervention type and content, population characteristics, and outcomes. Where possible, 'summary of findings' tables will be generated for each comparison. When data are available, we will calculate a risk ratio and its 95% CI (dichotomous outcomes) and/or effect size according to Cohen's formula (continuous outcomes) for the primary outcome of each trial. Ethics and dissemination: No ethical issues are foreseen. Findings will be disseminated widely to clinicians and researchers via journal publication and conference presentation(s). Prospero registration number: CRD42015025574.